1995
DOI: 10.1083/jcb.129.6.1641
|View full text |Cite
|
Sign up to set email alerts
|

7B2 facilitates the maturation of proPC2 in neuroendocrine cells and is required for the expression of enzymatic activity.

Abstract: Abstract. The prohormone convertase PC2, which is thought to mediate the proteolytic conversion of many peptide hormones, has recently been shown to interact with the neuroendocrine-specific polypeptide 7B2 in Xenopus intermediate lobe (Braks, J. A. M., and G. J. M. Martens. Cell 78:263. 1994). In the present work we have stably transfected neuroendocrine cell lines with rat 7B2 constructs and found that overexpression of 27 kD 7B2 greatly facilitates the kinetics of maturation of proPC2, both in AtT-20/PC2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
217
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(229 citation statements)
references
References 37 publications
11
217
1
Order By: Relevance
“…We have identified a CpG island (definition according to Gardiner-Garden and Frommer, 1987) that showed hypermethylation in 5 out of 10 medulloblastomas, but not in normal fetal cerebellum that was located 1.6 kb upstream of the initiator ATG within the 5 0 -UTR and first untranslated exon of the secretory granule neuroendocrine protein 1 gene (SGNE1; Figure 1a; modified from Mbikay et al, 2001 andStrausberg et al, 2002), the human homologue of the murine neuroendocrine gene 7B2. 7B2 binds to (Braks and Martens, 1994;Zhu and Lindberg, 1995) and functions as a specific chaperone for proprotein convertase-2 (PC2) and facilitates its movement toward the secretory pathway, where the zymogen is proteolytically matured and activated (Zhu and Lindberg, 1995). 7B2 is a member of a group of Ca 2 ĂŸ -dependent serine proteases that show homology to the endoproteases, subtilisin (bacteria) and kexin (yeast).…”
Section: Introductionmentioning
confidence: 99%
“…We have identified a CpG island (definition according to Gardiner-Garden and Frommer, 1987) that showed hypermethylation in 5 out of 10 medulloblastomas, but not in normal fetal cerebellum that was located 1.6 kb upstream of the initiator ATG within the 5 0 -UTR and first untranslated exon of the secretory granule neuroendocrine protein 1 gene (SGNE1; Figure 1a; modified from Mbikay et al, 2001 andStrausberg et al, 2002), the human homologue of the murine neuroendocrine gene 7B2. 7B2 binds to (Braks and Martens, 1994;Zhu and Lindberg, 1995) and functions as a specific chaperone for proprotein convertase-2 (PC2) and facilitates its movement toward the secretory pathway, where the zymogen is proteolytically matured and activated (Zhu and Lindberg, 1995). 7B2 is a member of a group of Ca 2 ĂŸ -dependent serine proteases that show homology to the endoproteases, subtilisin (bacteria) and kexin (yeast).…”
Section: Introductionmentioning
confidence: 99%
“…Using an in vitro binding assay, we previously showed that processed 7B2 associates with proPC2, but not with mature PC2 [17], indicating that processed 7B2 is indeed able to interact with the proregion of proPC2. Interestingly, Zhu and Lindberg recently demonstrated that the processed form of 7B2 facilitates production of enzymatically active PC2 in transfected cell lines [30]. Collectively, the results indicate that the N-terminal portion of 7B2 might well act as a chaperone for PC2.…”
Section: Discussionmentioning
confidence: 82%
“…SGNE1/7B2 binds inactive PC2 in the endoplasmatic reticulum preventing its premature activation in the regulated secretory pathway and facilitates its transport to later compartments where the zymogen is proteolytically matured and activated. 24,25 SGNE1/7B2 null mutants died of severe Cushing syndrome before 9 weeks of postnatal life whereas PC2 null mutants are viable. 26 Given the function of SGNE1/7B2 as a regulator of PC2 it is likely that the functional contribution of SGNE1/7B2 to the molecular pathology of gliomas is mediated through this protein family.…”
Section: Discussionmentioning
confidence: 99%